Implementation of Robust Optimization Model to Controlling the Inventory Costs of Consumable Medical Equipment at Malahayati Islamic Hospital - Linna Syahputri; Hendra Cipta (Jurnal Matematika, Statistika dan Komputasi, 2024)
Inventory management is critical to hospitals capacity to meet patient requests. Because of the fluctuating patient volume, hospitals frequently have trouble managing their inventory of consumable medical equipment. An optimization model must therefore be used to control inventories. One hospital that calculates inventory costs using traditional methods is Malahayati Islamic Hospital. This leads to high inventory expenses and storage costs when acquiring medical supplies like three-count syringes. anything meant to lower the cost of inventories. An optimization model that can use linear programming techniques to discover the optimal solution even in situations when the data is unclear is referred to as strong optimization. By applying a strong optimization model, it shows that the results of calculating the inventory costs of consumable medical equipment at the Malahayati Islamic Hospital can save costs of 24.71% of the total inventory costs of the Malahayati Islamic Hospital.